2017
DOI: 10.1007/s11060-017-2444-6
|View full text |Cite
|
Sign up to set email alerts
|

Key rates for the grades and transformation ability of glioma: model simulations and clinical cases

Abstract: Tumor progression to higher grade is a fundamental property of cancer. The malignant advancement of the pathological features may either develop during the later stages of cancer growth (natural evolution) or it may necessitate new mutations or molecular events that alter the rates of growth, dispersion, or neovascularization (transformation). Here, we model the pathological and radiological features of grades 2-4 gliomas at the times of diagnosis and death and study grade development and the progression to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Multiple studies of human glial tumors indicate that these tumors often undergo malignant transformation from low-grade tumors to high-grade malignant tumors. 11,13 Malignant transformation reflects increased rates of replication, angiogenesis, and migration due to genetic mutations. In contrast, higher numbers of mitotic figures were associated with a poor outcome in biopsies ( P = .0421) as well as in whole-brain samples, suggesting that this observation is a more robust histological feature in biopsies for prediction of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies of human glial tumors indicate that these tumors often undergo malignant transformation from low-grade tumors to high-grade malignant tumors. 11,13 Malignant transformation reflects increased rates of replication, angiogenesis, and migration due to genetic mutations. In contrast, higher numbers of mitotic figures were associated with a poor outcome in biopsies ( P = .0421) as well as in whole-brain samples, suggesting that this observation is a more robust histological feature in biopsies for prediction of outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The x -axis in (a–f) corresponds to the time interval from the baseline MRI. (g) The results of simulations of the mathematical model for grade 2 gliomas, showing percent of brain invaded by the tumor ( y -axis) as a function of the parameter for mitotic rate (per hour) in the presence of a low angiogenesis rate (0.1/hour), see Scribner et al [18]. (h) The curve fit of the normalized data of 14 patients with nonlinear growth using the model f(x) = a * exp( b * x ), coefficients (with 95% confidence bounds): a = 0.03751 (0.02759, 0.04743), b = 2.98 (2.69, 3.27), sum of squares due to error = 1.3701, r 2 = 0.8580. astro, astrocytoma; CAD, computer-assisted diagnosis; oligo, oligodendroglioma.…”
Section: Resultsmentioning
confidence: 99%
“…The authors have recently reported a system of partial differential equations (PDEs) that model glioma growth at the scale of MRI and pathology. The equations include the rates of replication (mitosis), brain invasion, angiogenesis, and a threshold for hypoxia; the numerical methods used to solve the system of PDEs are detailed elsewhere [18,28,29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of often rather well-defined margins on MRI, tumor cells are present outside the radiologically visible tumor, making this an infiltrative disease [3,4]. At an unpredictable point of time, LGG speed of growth increases due to malignant transformation [5,6]. Malignant transformation is a key clinical event and leads to intensified treatment, increased morbidity and premature death [7][8][9].…”
Section: Introductionmentioning
confidence: 99%